Tangentially symplectic foliations - Remsing, Claudiu Cristian (Rhodes University, Faculty of Science, Department of Mathematics, 1994)
This thesis is concerned principally with tangential geometry and the applications of these concepts to tangentially symplectic foliations. The subject of tangential geometry is still at an elementary stage. The author here systematises current concepts and results and extends them, leading to the definition of vertical connections and vertical G-structures. Tangentially symplectic foliations are then characterised in terms of vertical symplectic forms. Some significant particular cases are discussed.
Keywords: Geometry -- Problems, exercises, etc; Geometry, Differential; Symplectic manifolds; Poisson manifolds; Foliations (Mathematics)